Diversification of potato farming systems through legume intercropping for improved resource use efficiency - Nyawade, S. (2020)
Expanding production of potato to the midlands and lowlands of Kenya will only be possible if the effect of water deficit, high temperatures and nutrient limitation on potato growth is well understood. Potato (Solanum tuberosum L.) was grown singly and intercropped with lima bean (Phaseolus lunatus L.) or dolichos (Lablab purpureus L.), and the respective single crop of the legumes in three agro-ecological zones (AEZs) of Kenya; upper midland (1552 meters above sea level (masl)), lower highland (1894 masl) and upper highland (2552 masl). The objectives were as follows: i) determine the interelationships between soil water balance, soil temperatures and crop nutrient (NPK) uptake under potato-legume intercropping ii) assess the short-term effect of potato legume intercropping on dynamics of microbial activity and SOM fractions, iii) evaluate the effect of potato-legume intercropping on soil nitrogen balance and iv) quantify the radiation and crop water productivity of potato-legume intercropping system. The study was laid out in a randomized complete block design with four replications. All the potato treatments received basal fertilization at a rate of 50 kg N ha-1 , 90 kg P ha-1 and 100 kg K ha-1 and topdress of 40 kg N ha-1 . Soil temperatures and soil water contents (SWC) were quantified at different stages of potato growth. Residues from each cropping system were quantified at the end of each season and incorporated back into the soil at start of the subsequent season. Soil samples (0–120 cm depths) were taken at the interrows of each plot prior to planting, at vegetative growth, and at the end of each season. Physical and density fractionation procedure was used to separate the soil in macro-aggregates (>250 μm), micro-aggregates (250–50 μm) and silt plus clay fractions (<50 μm), while SOM was partitioned into labile (density of 1.65 to 1.85 g cm−3) and stable (2.60 g cm−3) fractions. Microbial biomass carbon was determined by chloroform fumigation while enzymatic activities were assessed by hydrolyses of fluorescein diacetate and dehydrogenase. Nitrogen gains from mineralization, fertilization, and outputs from biomass accumulation, leaching, and soil erosion were quantified throughout the potato growth cycle. N losses through volatilization were quantified using ventilation chambers while the amount of N leached was extracted using solusamplers located at vertical depths of 0–1.5 m and the leachetes analyzed for nitrate contents. Leaf area index (LAI) and light interception were quantified at different stages of potato growth and related with the radiation use efficiency (RUE) and crop water productivity (CWP). The data was subjected to mixed model analyses of variance using R software with Tukeys mean separation test set at 95% propability level. Intercropping increased LAI by 26–57% relative to sole potato and significantly (p < 0.05) lowered soil temperatures in the 0–30 cm depth by up to 7°C. This increased SWC by up to 38%, thus increasing RUE by 56–78%, CWP by 45–67% and nutrient use efficiency by 40–67%. Compared with the sole potato, intercropping increased the contents of labile fraction organic matter by 12–28%, dissolved organic matter by 7–21% and microbial biomass by 15–38%, thus stimulating enzyme activities. Trends in soil microbial respiration followed those of enzyme activity and were 20–34% higher in intercropping than in sole potato. Soil N balance was significantly influenced by legume intercropping (p<0.05) and ranged between -10.7 to -18.1 kg N ha-1 for sole potato, 4.1 to 6.6 kg N ha-1 for intercropping and 2.9 to 22.3 kg N ha-1 for sole legumes. The residue mixture of potato and legume intercrops enhanced N mineralization with peak N release of 5 to 9 kg N ha-1 occurring within 8 to 10 weeks of residue decomposition. This period coincided with the peak N uptake by potato (19.9 to 31.2 kg N ha-1 ) thus showing a close synchrony of N supply and potato N demand. These results provide a possible entry point to restoring the impoverished soil productivity in the smallholder potato farming systems and offer the possibility of potato expansion to midland agro-food systems.